Copenhagen Burnout Inventory On A National Representative Sample Of Pre-School Teachers. (13th November 2019) - Piperac, P; Terzic-Supic, Z; Todorovic, J; Maksimovic, A; Karic, S; Santric-Milicevic, M
Abstract: Background: Pre-school teachers are faced with work-related stress and are at increased risk of development of burnout syndrome. The aim of this study was to evaluate the reliability of the Serbian version of Copenhagen burnout inventory (CBI) on a National Representative Sample of preschool teachers in Serbia. Methods: This was a cross-sectional study conducted between October 2018 and April 2019 which included 456 preschool teachers in Serbia. The instrument contained questions on socio-demographic, socio-economic characteristics, lifestyle characteristics, workplace environment and Serbian version of CBI. Univariate linear regression, multiple linear regression, Cronbach alpha coefficients were performed. Results: Cronbach alpha of three domains of CBI were: personal burnout-0.907, work-related burnout-0.878, client-related burnout- 0.903. Multiple linear regression analysis showed that having a tenured contract (ß=3.46, p = 0.04), working in shifts (ß=7.94, p = 0.01), and having worse self-perceived health status (ß=-8.88, p = 0.01) were significantly associated with personal burnout. Working in shifts (ß=-4.67, p-0.012) and having worse self-perceived health status (ß=-7.82, p < 0.001) were significantly associated with work-related burnout. Age (ß=0.53, p < 0.001), living in urban areas (ß=-6.55, p = 0.015), alcohol consumption (ß=5.09, p = 0.016), number of children teacher work with (ß0.407, p = 0.005), having teaching equipment (ß=-4.46, p = 0.033), and having worse self-perceived health status (ß=-7.17, p < 0.0001) were significantly associated with client-related burnout. Conclusions: CBI is a valid instrument for the assessment of burnout among preschool teachers in Serbia. Many workplace-related factors, which could be subject of preventive measures, are associated with domains of burnout in this population. Key messages: Workplace-related factors are associated with burnout among preschool teachers in Serbia. CBI is valid instrument for assessment of burnout among preschool teachers.